Pathological Personality Traits and Intimacy Processes Within Roommate Relationships. Issue 2 (March 2015) - Ackerman, Robert A.; Corretti, Conrad A.
Abstract: Problems with intimacy constitute an important area of interpersonal dysfunction in those with personality pathology. Drawing on the interpersonal process model of intimacy, the present research used a longitudinal dyadic design of same‐sex roommate pairs (n = 103) to address how certain pathological personality traits (i.e. Negative Affect, Detachment, and Antagonism) relate to the development of disclosure, perceived responsiveness, and closeness. We expected that participants' pathological traits would be linked to both their own and their roommate's intimacy development, and that the mechanisms underlying these links would include the endorsement of interpersonal values and/or the dispositional expression of interpersonal behaviour in the roommate relationship. Our findings demonstrate that interpersonal motives and/or behaviours primarily help to explain how individuals with higher levels of Detachment manifest difficulty with intimacy. Implications of our findings for research on personality pathology, normative traits, and intimacy are discussed. Copyright © 2015 European Association of Personality Psychology